Influence of FTO rs9939609 polymorphism on appetite, ghrelin, leptin, IL6, TNFα levels, and food intake of women with morbid obesity - Magno FCCM (Dove Medical Press, 2018)
Fernanda Cristina Carvalho Mattos Magno,1 Helena Chrispim Guaraná,1 Ana Carolina Proença Fonseca,2 Giselda Maria Kalil Cabello,2 João Régis Ivar Carneiro,3 Aline Pereira Pedrosa,1 Ana Carolina Ximenes,1 Eliane Lopes Rosado1 1Institute of Nutrition, Federal University of Rio de Janeiro, Rio de Janeiro, RJ, Brazil; 2Oswaldo Cruz Foundation (FIOCRUZ), Oswaldo Cruz Institute (IOC), Human Genetics Laboratory, Rio de Janeiro, RJ, Brazil; 3Federal University of Rio de Janeiro, University Hospital Clementino Fraga Filho, Service of Nutrology, Rio de Janeiro, RJ, Brazil Background: The fat mass and obesity-related (FTO) gene has a strong relationship with obesity, extreme obesity and inflammatory state, and may also be associated with food intake regulation.Objective: The aim of the present study was to evaluate the influence of the rs9939609 single-nucleotide polymorphism of the FTO gene on appetite, ghrelin, leptin, interleukin 6 (IL6), tumor necrosis factor α (TNFα) levels and food intake of morbidly obese women.Materials and methods: The study comprised 70 women, aged between 20 and 48 years, from Rio de Janeiro, Brazil. The participants were selected according to the body mass index between 40 and 60 kg/m2. Anthropometric and biochemical data were measured during fasting. Hormones and inflammatory data were measured before and after the participants ate an isocaloric meal. Dietary records were calculated and analyzed using a nutritional assessment program. Visual analog scales were used for behaviors of the sensations of appetite and food preferences. The FTO rs9939609 variant was genotyped using real-time polymerase chain reaction.Results: Participants with the AA genotype had lower values of ghrelin and IL6 and higher values of leptin than those with TT and TA in the postprandial period. Comparing the plasma concentrations of ghrelin, insulin, IL6 and TNFα intragenotypes, it was observed that those with TT had decreased leptin and increased IL6 at the postprandial period. Subjects with TA showed increased postprandial IL6, and those with AA had decreased postprandial ghrelin. There was no difference in TNFα intra- and intergenotypes. The postprandial sensations of hunger were lower in AA than those with TT. There were differences between genotypes regarding ingested grams of protein by weight, cholesterol, B3, B5, B6 and B12 vitamins, and selenium potassium and sodium minerals.Conclusion: These findings suggest that genetics may exert an influence on physiologic factors and might alter eating behavior. Keywords: obesity, rs9939609, hormones, inflammatory cytokines, food intake, binge eating